1993
DOI: 10.1101/gad.7.10.1850
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of the transcription factors E2F-1 and DP-1 leads to cooperative trans-activation.

Abstract: The E2F transcription factor has been implicated in the regulation of genes whose products are involved in cell proliferation. Two proteins have recently been identified with E2F-like properties. One of these proteins, E2F-1, has been shown to mediate E2F-dependent trans-activation and to bind the hypophosphorylated form of the retinoblastoma protein {pRB). The other protein, mudne DP-1, was purified from an E2F DNA-affinity column, and it was subsequently shown to bind the consensus E2F DNA-binding site. To s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
486
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(513 citation statements)
references
References 63 publications
24
486
0
3
Order By: Relevance
“…The following expression vectors were used: bgalactosidase: pEQRSVb-Gal; luciferase: pSV2-luc; E2F-1: pCMVE2F-1 (Helin et al, 1993a); E2F-4-NLS: pCMVHAE2F-4-NLS (MuÈ ller et al, 1997); hemagglutinintagged DP-1 (Helin et al, 1993b) and mutant derivatives: pCMVHADP-1, pCMVHADP-1 D103 ± 126 , and pCMVHADP-1 127 ± 410 .…”
Section: Plasmidsmentioning
confidence: 99%
“…The following expression vectors were used: bgalactosidase: pEQRSVb-Gal; luciferase: pSV2-luc; E2F-1: pCMVE2F-1 (Helin et al, 1993a); E2F-4-NLS: pCMVHAE2F-4-NLS (MuÈ ller et al, 1997); hemagglutinintagged DP-1 (Helin et al, 1993b) and mutant derivatives: pCMVHADP-1, pCMVHADP-1 D103 ± 126 , and pCMVHADP-1 127 ± 410 .…”
Section: Plasmidsmentioning
confidence: 99%
“…Particularly noteworthy among these are the interactions with the E2F/DP family of transcription factors (Cao et al, 1992;Devoto et al, 1992;Helin et al, 1992Helin et al, , 1993Kaelin et al, 1992;Shan et al, 1992;Shirodkar et al, 1992;Cobrinik et al, 1993;Ivey-Hoyle et al, 1993;Lees et al, 1993;Bandara et al, 1994;Bejersbergen et al, 1994;Ginsberg et al, 1994;Buck et al, 1995;Hijmans et al, 1995;Ormondroyd et al, 1995;Sardet et al, 1995;Wu et al, 1995;Zhang and Chellappan, 1995). The E2F transcription factors are thought to control expression of a number of genes involved in cell cycle progression (reviewed in Cobrinik, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The E2F transcription factors are thought to control expression of a number of genes involved in cell cycle progression (reviewed in Cobrinik, 1996). The interactions between the Rb family members and E2F members e ectively inhibit E2F-mediated transactivation (Hamel et al, 1992;Heibert et al, 1992;Weintraub et al, 1992;Zamanian and LaThangue, 1992;Flemington et al, 1993;Helin et al, 1993;Schwartz et al, 1993;Zamanian and LaThangue, 1993;Zhu et al, 1993;Beijersbergen et al, 1994;Ginsberg et al, 1994;Johnson, 1995;Smith and Nevins, 1995;Vairo et al, 1995). Interactions involving pRB or p107 and various other cellular proteins, including other transcription factors, also have been described (reviewed in Whyte, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…12 The ability of E2F-1 to associate with another E2F-like protein, DP-1, confers a synergistic effect on transcriptional activity. 13 Moreover, E2F-1 operates under the tight control of cell-cycle machinery, with its peak expression at the G 1 /S boundary. 14 Several recent studies have indicated that E2F-1 may have functions besides promoting entry into the S phase.…”
mentioning
confidence: 99%